Incorporating Surgery in treatment of Stage IIIA – N2 Non- Small Cell Lung Cancer - Thakur, Binay; Devkota, Mukti (Nepalese Journal of Cancer, 2021)
Stage IIIA-N2 Non-small cell lung cancer includes heterogenous group of patients with a poor 5-year survival ranging from 13% to 36% with surgery alone. Various randomized controlled trials established the role of multimodality treatment either including or excluding surgical resection. In a select group of non-bulky/ single station N2 disease, the better results have been achieved with induction chemotherapy or chemo-radiotherapy followed by surgery.